Neonatal Disease Distribution and Admission Outcomes at the District Hospital: Neonatal Disease Distribution and Admission Outcomes - Talreja, Washdev; Aman , Suhail; Hussain , Wajid; Hussain, Zahid; Jhatial, Irfan Ali; Kewalani, Sapna; Baloch, Zainab; Parial Shahani, Muhammad (Pakistan Journal of Health Sciences, 2022)
The most vulnerable time for a newborn is during the neonatal period. The important factors affecting neonatal mortality during the first 28 days of life include poor antenatal care for mothers, inadequate treatment during birth, or lack of skillful care. With a rate of 48 per 1000 live births, Pakistan is ranked third in the world. This is because it accounts for 7% of all neonatal deaths globally. In Pakistan one in every 22 newborns dies within the first month of life. Objective: To evaluate the frequency and distribution of neonatal morbidity patterns and admission outcomes in district hospital Dadu, Sindh, Pakistan. Methods: A descriptive cross-sectional study was conducted at the Civil Hospital Dadu which is a district hospital in Sindh. The data was obtained in 2020. Using universal sampling method, neonates’ gender, age at the time of the birth, disease patter and admission outcome were recorded. Data was analyzed in Microsoft Excel 2010. Results: Out of total 1637 admitted neonates there were 411 (25.1%) case of sepsis, BA 17.16%, preterm 14.9%, LBW 13.81%. Amongst, 789 (48.1%) were discharged after improvement, and 251(15.3%) neonates died. Conclusions: Less than half of the newborns who were admitted could improve during the admission. More than 15% of newborn deaths are alarming. The policymakers should take action to reduce early neonatal mortality by effectively managing neonatal illnesses